Treatment of Acute Decompensated Chronic Heart Failure: Furosemide vs Furosemide and Metolazone: A Cross-Sectional Comparative Study - Risal, Ujjwol Prasad; Karki, Prahlad; Shah, Prashant (Nepalese Heart Journal, 2022)
Background: Heart failure is a leading cause of hospital admissions each year. In Nepal also the incidence of heart failure is increasing. Acute decompensated heart failure carries a poor prognosis. Most patients respond to intravenous loop diuretics but a substantial proportion of patients are resistant to them and may need additional diuretic agents like metolazone by the principle of “sequential nephron blockade”.Methods: In a hospital-based cross-sectional comparative study, we assigned 68 patients with acute decompensated chronic heart failure patients to receive furosemide at 1 mg/kg twice daily or furosemide at 1 mg/kg twice daily plus metolazone 5mg/day. The primary end-points were daily weight loss, negative water balance (difference between urine output and fluid intake) and symptomatic improvement on NYHA grading.Results: There were 55% males and 45% females in total. There was a significant difference (p-value =0.003) in mean weight loss observed between the two groups on day three, i.e., 0.971±0.6 kg and 1.5±0.78 kg in furosemide group and furosemide plus metolazone group respectively. Mean negative water significantly more in the combination group on day two (450±230.94 ml vs 750.59±416.92 ml) with p-value